Eksplorasi Akuntabilitas dan Transparansi dalam Pengelolaan Dana Zakat pada Baznas Kabupaten Sumbawa - Septi Ramdayanti; Denny Hambali (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
Zakat is an Islamic economic instrument that plays a significant role in enhancing social welfare and promoting equitable socioeconomic development. The effectiveness of zakat management is strongly influenced by the accountability and transparency practices implemented by zakat management institutions. This study aims to explore the practices of accountability and transparency in zakat fund management at the National Board of Zakat (BAZNAS) of Sumbawa Regency and to examine their contribution to public trust. A descriptive qualitative approach was employed, with data collected through interviews, observations, and document analysis. The findings reveal that accountability has been implemented through financial reporting in accordance with PSAK 109, external auditing, and structured accountability mechanisms. Transparency is demonstrated through the dissemination of information via the official website, social media platforms, print media, and public outreach activities. The implementation of these principles contributes to strengthening the trust of muzakki (zakat payers) and generating tangible benefits for mustahik (zakat beneficiaries), although improvements in information accessibility and the development of productive zakat programs remain necessary. The novelty of this study lies in its exploration of the interrelationship between accountability, transparency, muzakki trust, and the perceived benefits experienced by mustahik within the context of regional zakat management at BAZNAS Sumbawa Regency.